2002
DOI: 10.1289/ehp.110-1241242
|View full text |Cite
|
Sign up to set email alerts
|

The role of biomethylation in toxicity and carcinogenicity of arsenic: a research update.

Abstract: Recent research of the metabolism and biological effects of arsenic has profoundly changed our understanding of the role of metabolism in modulation of toxicity and carcinogenicity of this metalloid. Historically, the enzymatic conversion of inorganic arsenic to mono- and dimethylated species has been considered a major mechanism for detoxification of inorganic arsenic. However, compelling experimental evidence obtained from several laboratories suggests that biomethylation, particularly the production of meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 256 publications
(147 citation statements)
references
References 34 publications
5
137
0
3
Order By: Relevance
“…However, no details regarding the speciation technique or data validation are provided. Our studies on the metabolism and toxic effects of As in UROtsa cells (Drobná et al, 2003;Styblo et al, 2000Styblo et al, , 2002 have consistently shown that these cells do not methylate iAs. Notably, T24 cells, another cell line derived from human bladder epithelium, also lack the capacity to methylate iAs (Styblo et al, 2000).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, no details regarding the speciation technique or data validation are provided. Our studies on the metabolism and toxic effects of As in UROtsa cells (Drobná et al, 2003;Styblo et al, 2000Styblo et al, , 2002 have consistently shown that these cells do not methylate iAs. Notably, T24 cells, another cell line derived from human bladder epithelium, also lack the capacity to methylate iAs (Styblo et al, 2000).…”
Section: Discussionmentioning
confidence: 58%
“…Confluent cell cultures were serum starved for 16 h before use in experiments. These or similar culture conditions, including serum starvation, have previously been used by this and other laboratories in studies that examined the metabolism and toxic effects of iAs in UROtsa cells (Drobná et al, 2003;Simeonova et al, 2000Simeonova et al, , 2002Styblo et al, 2000Styblo et al, , 2002. Notably, serum starvation for 16 h had no effect on the integrity or morphology of cultured cells.…”
Section: Cell Lines and Cell Culturementioning
confidence: 94%
“…However, recent studies have suggested that the main intermediate metabolites MA (III) and DMA (III) are reactive and highly toxic in themselves, resulting in the current view that the metabolic products of iAs metabolism probably have a role in the mechanism of As toxicity [14,76,110]. Generally, trivalent arsenicals are more toxic than the pentavalent [14,111], and MA (III) and DMA (III) are rapidly oxidized to their pentavalent counterparts [112,113]. These intermediates in the iAs methylation scheme can initiate toxic effects, like DNA-damage [114,115], or be indirectly genotoxic [110,116].…”
Section: Mechanisms and Toxicity Of Arsenic Compounds Occurring In Sementioning
confidence: 99%
“…Human metabolism of iAs involves the reduction of As(V) to As(III) and the oxidative methylation of As(III)-species that yields methylated arsenicals containing either As(III) or As(V) [1][2][3]. Toxicities of tri-and pentavalent iAs and methylated arsenicals differ significantly [4][5][6]. Therefore, developing methods for the oxidation state specific speciation analysis of As in biological matrices has become a key issue for As toxicology and analytical chemistry.…”
Section: Introductionmentioning
confidence: 99%